Efficacy of Azithromycin in Enteric Fever in Children - Jamil, Saima; Anis ur Rahman,; Shamraiz, Afnan (Indus Journal of Bioscience Research, 2025)
Background: Enteric fever remains a significant child health condition, and effective and early use of antibiotics is crucial to reduce morbidity. Azithromycin is widely employed due to its favorable pharmacokinetics and intracellular activity against Salmonella typhi. Treatment outcomes according to different demographics and clinical syndromes should be investigated further. Objective: To determine the efficacy of Azithromycin in children with enteric fever at Abbottabad international hospital. Study Design: Descriptive cross-sectional study. Duration and Place of Study: Conducted from June 2024 to December 2024 at the Department of Pediatrics, Abbottabad International Hospital, Abbottabad. Methodology: A total of 87 children aged 3–15 years with culture-confirmed enteric fever were enrolled. All participants received supervised oral azithromycin at 20 mg/kg/day for five days. Clinical efficacy was defined as complete symptom resolution within seven days of therapy initiation. Data on demographic characteristics, clinical parameters, and treatment outcomes were collected and analyzed using appropriate statistical tests. Results: The average was 8.17 ± 3.54 years, and 73.6% of them were males. The overall efficacy was 75.9%. Duration of fever was significantly correlated with success of treatment; 92.6% was seen in patients with fever ≤10 days, while 48.5% was observed in patients having fever for more than 10 days (p=0.000). No correlation was observed for efficacy and age, gender, weight, socioeconomic status, or place of residency. Conclusion: Azithromycin is effective for the treatment of enteric fever among children, and early initiation of treatment produces better clinical outcomes.